Mechanical design of a Cartesian robot - Fekete, Dániel; Rónai, László; Lénárt, József (Design of Machines and Structures, 2024)
This paper investigates the assembling options of a cartesian type robot, which can be used for material handling or 3D printing purposes. The structure has three ball screw driven linear units, which will be controlled by a microcontroller. The requirements of the structure to use as a 3D printer are defined. The solution selection matrix is constructed in order to choose the appropriate configuration of the system.